First-principle study of electronic structure and optical properties of SiC nano films. (9th October 2019) - Niu, Yanan; Hu, Huijun; Zhang, Wenshu; Li, Jianguo; Qiao, Liqing; Dong, Nan; Han, Peide
Abstract: The structure, electronic and optical properties of 3C–SiC nano films were calculated according to first principles based on density functional theory. It is manifested that the nano films were structurally stable when the number of layers was increased to 12. Compared with bulk counterparts, nano films displayed narrower band gaps, and their Fermi energy levels were brought into the conduction band. The ε 2 ( ω ) of dielectric function, extinction coefficient, and absorption coefficient of the nano films were greater than that of the bulk in the ultraviolet range. With the layer numbers decreased, the values increased in the range. The results provide a guideline for 3C–SiC nano films to work for UV detectors.